دور ثقافة الجودة في تعزيز جودة الخدمة التعليمية: بحث تحليلي لآراء أساتذة وطلبة الدراسات العليا بكلية التربية البدنية وعلوم الرياضة جامعة كربلاء - عبدالله، حسين علي; الدليمي، محمود فهد عبد علي; الشمري، أحمد عبدالله أمانة (جامعة بابل - كلية الإدارة والاقتصاد, 2022)
هدف البحث لمعرفة دور ثقافة الجودة في تعزيز جودة الخدمة التعليمية بكلية التربية البدنية وعلوم الرياضة بجامعة كربلاء، إذ شخصت مشكلة البحث بمجموعة تساؤلات تضمنت مستوى إدراك العلاقة بين متغيرات البحث ميدانيًا، إذ اعتمد على مقياس Bendermacher et al, 2019)) لقياس ثقافة الجودة، والذي يتكون من عشرة أبعاد (العلاقات بين الأفراد، العمليات الداخلية، الهدف الرشيد، الأنظمة المفتوحة، القيادة، الاتصالات، التمكين، الالتزام، الملكية وتحسين الجودة). في حين تم قياس متغير جودة الخدمة التعليمية بالاعتماد على مقياس Abdullah, 2006)) الذي يتضمن خمسة أبعاد هي (الجوانب الأكاديمية، الجوانب غير الأكاديمية، السمعة، الوصول والبرامج). وقد تمثلت عينة البحث بـ 60 أستاذ وطالب في الدراسات العليا بالكلية المبحوثة، واستخدمت الاستبانة كأداة رئيسية لجمع البيانات، ولغرض التحليل الإحصائي اعتمد على تحليل الانحدار، الارتباط، التحليل العاملي الاستكشافي. إذ توصل البحث لمجموعة من الاستنتاجات منها، اهتمام الكلية المبحوثة بتطبيق منهج ثقافة الجودة الذي يعزز جودة الخدمة التعليمية. The aim of the research is to know the role of quality culture in enhancing the quality of educational service at the College of Physical Education and Sports Sciences at the University of Karbala, as the research problem was diagnosed with a set of questions that included the level of awareness of the relationship between research variables in the field, as it was based on the scale (Bendermacher et al) 2019 to measure the culture of quality, which It consists of ten dimensions (interpersonal relations, internal processes, rational purpose, open systems, leadership, communication, empowerment, commitment, ownership and quality improvement). While the educational service quality variable was measured based on the (Abdullah) 2006 scale, which includes five dimensions (academic aspects, non-academic aspects, reputation, access and programs). The research sample was represented by 60 professors and students in graduate studies at the researched college, and the questionnaire was used as a main tool for data collection, and for the purpose of statistical analysis it relied on regression analysis, correlation, exploratory factor analysis. As the research reached a set of conclusions, including the interest of the college under study in applying the quality culture approach that enhances the quality of educational service.
Keywords: ثقافة الجودة -- تحسين الجودة -- الخدمات التعليمية -- التميز الإداري -- التعليم الجامعي -- المؤسسات الجامعية